Who's to blame? The role of power and attributions in susceptibility to match-fixing. (July 2021) - O'Shea, Deirdre; Barkoukis, Vassilis; McIntyre, Tadhg; Loukovitis, Andreas; Gomez, Carole; Moritzer, Severin; Michaelides, Michalis; Theodorou, Nikolaos
Abstract: Objective: Official reports and anecdotal evidence suggest that people with power frequently put pressure on athletes to fix a match. Therefore, it is assumed that athletes may attribute their involvement to this pressure. The present study was designed to investigate the role that power, attributions and moral emotions may play in the decision to fix a match. Method: Team and individual sport athletes ( N  = 427) competing in five European countries participated in a quasi-experimental vignette design. Participants completed eight vignettes manipulating power, source of attributions and stability of attributions. Match-fixing susceptibility and five discrete anticipated moral emotions (guilt, shame, pride, indifference, anger) were measured. Results: The results of the analyses demonstrated that athletes are perceived to be most susceptible to match-fixing when the reason is related to a stable attribute of the individual (e.g., enjoying gambling, having a betting problem). However, participants reported also being susceptible to match-fixing when power is high. Anticipated emotions negatively predicted match-fixing susceptibility and mediated the effect of attributions and power on match-fixing susceptibility. Conclusion: The findings provide information on the interplay between attributions, power and anticipated emotions in predicting match-fixing susceptibility, and the determinants of match-fixing susceptibility. This will be of benefit to policy makers, sporting organizations and researchers in developing policies and interventions to protect athletes from being vulnerable to match-fixing requests. Highlights: Athletes are perceived to be most susceptible to match-fixing when related to a stable attribute of the individual (e.g., enjoying gambling). However, athletes are also susceptible to match-fixing when they receive a request from a person in a position of power. Anticipating negative emotions one may experience if one engages in match-fixing is a protective factor.